The Acute Effects of Caffeine Supplementation on Anaerobic Performance and Functional Strength in Female Soccer Players - Mor, Hakki; Mor, Ahmet; Abdioglu, Mekki; Tohanean, Dragos Ioan; Savu, Catalin Vasile; Acar, Gizem Ceylan; Moraru, Cristina Elena (Mdpi, 2025)
Background/Objectives: Despite extensive research on caffeine's (CAF's) ergogenic effects, evidence regarding its impact on anaerobic performance in female athletes remains limited and inconclusive. The aim of this study was to investigate the acute effects of 6 mg/kg(-1) caffeine on anaerobic performance, functional strength, agility, and ball speed in female soccer players. Methods: A randomized, double-blind, placebo-controlled crossover design was employed. Thirteen moderately trained female soccer players (age: 21.08 +/- 1.11 years; height: 161.69 +/- 6.30 cm; weight: 59.69 +/- 10.52 kg; body mass index (BMI): 22.77 +/- 3.50 kg/m(2); training age: 7.77 +/- 1.16 years; habitual caffeine intake: 319 +/- 160 mg/day) completed two experimental trials (caffeine vs. placebo (PLA)), separated by at least 48 h. Testing sessions included performance assessments in vertical jump (VJ), running-based anaerobic sprint test (RAST), bilateral leg strength (LS), handgrip strength (HS), single hop for distance (SH), medial rotation (90 degrees) hop for distance (MRH), change of direction (COD), and ball speed. Rating of perceived exertion (RPE) was also recorded. Results: CAF ingestion significantly improved minimum (p = 0.011; d = 0.35) and average power (p = 0.007; d = 0.29) during RAST. A significant increase was also observed in SHR (single leg hop for distance right) performance (p = 0.045; d = 0.44). No significant differences were found in VJ, COD, ball speed, LS, HS, SHL, MRHR, or MRHL (p > 0.05). RPE showed a moderate effect size (d = 0.65) favoring the CAF condition, though not statistically significant (p = 0.110). Conclusions: In conclusion, acute CAF intake at a dose of 6 mg/kg(-1) may enhance anaerobic capacity and lower-limb functional strength in female soccer players, with no significant effects on jump height, agility, or upper-body strength.
Keywords: caffeine; anaerobic performance; female soccer players; functional strength; ball speed